AFM analysis of collagen fibrils in expanded scalp tissue after anisotropic tissue expansion - Aziz, Jazli; Ahmad, Muhamad Fadhil; Rahman, Mohammad Tariqur; Yahya, Noor Azlin; Czernuszka, Jan; Radzi, Zamri (Elsevier, 2018)
Successful use of tissue expanders depends on the quality of expanded tissue. This study evaluates the impact of anisotropic self-inflating tissue expander (SITE) on the biomechanics of skin. Two different SITE were implanted subcutaneously on sheep scalps; SITE that requires 30 days for maximum expansion (Group A; n = 5), and SITE that requires 21 days for maximum expansion (Group B; n = 5). Control animals (n = 5) were maintained without SITE implantation. Young's Modulus, D-periodicity, overlap and gap region length, diameter, and height difference between overlap and gap regions on collagen fibrils were analyzed using atomic force microscopy. Histology showed no significant differences in dermal thickness between control and expanded skin of groups A and B. Furthermore, most parameters of expanded skin were similar to controls (p > 0.05). However, the height difference between overlap and gap regions was significantly smaller in group B compared to both control and group A (p < 0.01). Strong correlation was observed between Young's Modulus of overlap and gap regions of the control and group A, but not group B. Results suggest that a relatively slower SITE can be useful in reconstructive surgery to maintain the biomechanical properties of expanded skin.